Reirradiation of locally recurrent nasopharyngeal cancer: history, advances, and promises for the future - Kong, Lin; Lu, Jiade J. (Chinese Clinical Oncology; Vol 5, No 2 (April 19, 2016): Chinese Clinical Oncology (Nasopharyngeal Carcinoma-Guest Editors: Joseph Wee, Yoke-Lim Soong, Melvin Chua), 2016)
Local or locoregional recurrence of nasopharyngeal carcinoma (NPC) after high-dose radiotherapy remains a significant clinical problem. This is especially important in regions of the world in which NPC is endemic, such as Southern China. In this review, we briefly present the evolution in the definitive treatment of NPC, but focus more so on the historical and contemporary treatment approaches and outcomes utilized in the recurrent setting. Specifically, we highlight the various treatment strategies (repeat surgery, brachytherapy, conventional re-irradiation, SRS/SBRT, and salvage IMRT), and their technical, physical and biological limitations. Special attention is given towards salvage IMRT, as this is becoming the standard of care for locally recurrent NPC. Further, it is the most commonly indicated modality, since it can be used to treat larger tumors and more extensive disease stages, which represent the majority of recurrent cases. Predictive and prognostic factors for the efficacy of repeat treatment are discussed as well. The toxicities brought about by repeat radiotherapy courses are also highlighted, with an emphasis on their impact on mortality and quality of life, which underscore the difficulty that this clinical entity presents. Lastly, the rationale for particle radiation therapy, which is potentially safer and more efficacious, for the treatment of locally recurrent NPC is presented.